The chicken skeletal muscle alpha-actin promoter is tissue specific in transgenic mice. - Petropoulos, C J (1989)
We have generated transgenic mouse lines that carry the promoter region of the chicken skeletal muscle alpha (alpha sk) actin gene linked to the bacterial chloramphenicol acetyltransferase (CAT) gene. In adult mice, the pattern of transgene expression resembled that of the endogenous alpha sk actin gene. In most of the transgenic lines, high levels of CAT activity were detected in striated muscle (skeletal and cardiac) but not in the other tissues tested. In striated muscle, transcription of the transgene was initiated at the normal transcriptional start site of the chicken alpha sk actin gene. The region from nucleotides -191 to +27 of the chicken alpha sk actin gene was sufficient to direct the expression of CAT in striated muscle of transgenic mice. These observations suggest that the mechanism of tissue-specific actin gene expression is well conserved in higher vertebrate species.